English Language Learners in Higher Education: An Exploratory Conversation - Harrison, Jamie; Shi, Hong (Journal of International Students, 2016)
This article discusses an exploratory conversation between a newly hired assistant professor of ESOL Education and one of her graduate level students taking the methods and materials course. The graduate student was an English learner (international student), and therefore offered this new professor an opportunity to explore her practice of working with English learners in a new context outside of K-12 schools. The discussion followed theoretical protocols of cogenerative dialogue in which the student brought in artifacts from the recently completed course that exemplified easy and difficult assignments. Both professor and student were able to examine their own practices in relation to access of curriculum and strategies that encourage that access.